Study on utilization of blood and blood components in surgical patients in a tertiary care hospital in Himachal Pradesh, India - Vyas, Vipasha; Taggar, Gurpreet Kaur; Malhotra, Sandeep (International Journal of Research in Medical Sciences, 2025)
Background: This study aims to assess the utilization patterns and appropriateness of blood and blood components and evaluate transfusion practices across various surgical procedures. Methods: A one-month record based cross sectional retrospective study involving 1392 patients fulfilling the inclusion criteria for surgical procedures has been conducted at the department of immunohematology and blood transfusion, Indira Gandhi Medical College and Hospital, Shimla, India. Results: Out of 1392 patients enrolled, females accounted for 746 (53.6%) and males for 646 (46.4%). Surgical procedures have been broadly classified as elective and emergency. Among elective procedures most commonly performed was cholecystectomy 394 (28.3%), least common was involving surgery for Ca breast 7 (0.5%) and Ca prostate 7 (0.5%). Among emergency procedures the highest proportion was orthopaedic surgeries 143 (10.2%), lowest proportion was herniorrhaphy 12 (0.8%) and extradural haemorrhage 12 (0.8%). After further scrutinizing the data, it was found that among elective procedures, cholecystectomy, appendectomy, H. cyst, Ca Breast, Ca Prostate, Ca Colon, orthopaedics, transurethral resection of prostate (TURP), cardio-thoracic and vascular surgeries (CTVS) demonstrated a crossmatch to transfusion (C/T) ratio below 2.5, transfusion probability (TP) below 30% and transfusion index (TI) >0.5%. However, herniorrhaphy and burns demonstrated a C/T ratio>2.5, TP > 30% and TI >0.5%. Among emergency procedures, cholecystectomy, appendectomy, peritonitis, intestinal obstruction, intussusception, RSA, fracture, EDH, SDH, SAH demonstrated a C/T ratio below 2.5, TP below 30% and TI >0.5%. Conclusions: Blood utilization practice for both emergency and elective surgical procedures appear effective with CT ratio of 1.2, TP 80.6 and TI 0.8.